PERAN SISTEM INFORMASI DALAM PENGAMBILAN KEPUTUSAN DI DIVISI SUMBER DAYA MANUSIA STUDI PADA PT XYZ - , Dwi Kurniyati, Dr. Sumiyana, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Conditions of palm oil plantations that are very vast and scattered in various remote locations have an impact on the growing volume of data and information that is increasingly complex. There are several important factors in the effective management of oil palm plantations which include the availability of accurate and adequate information for plantation activities and answer the demands of the company . Transactional-based information systems, in general supports decision making within an organization. Therefore it is still very relevant to view the role of information systems applied in the human resources division in decision-making and play a role in improving the quality of decision-making as a matter of research. Data collected by a survey was conducted about employee opinion in the year 2011 - 2012 and the interviews used an interview guide to help all levels of decision-makers, among others: the manager, general manager or group leader and director. The study was conducted in a group of companies, namely PT. XYZ with the first phase of the research scope of application of information systems. From the survey results, it appears that 86 % of employees agreed that the information system allows users to make decisions. The issues in corporate decision of both the technical and strategic in the area of human resource management function are because of lack of implementation of information systems. The quality of the better decisions because of the information and statements are very easily accessible and integrated online . Thus the problem of human error in the compilation of data and information to corporate delay does not happen againAnother perceived advantage of information system for decision-makers are: the existing reports can be withdrawn at any time and the report can be drawn by anyone who has access to the system, but is regulated through a security matrix and tree department that has been defined previously. For corporate interests, the report can be withdrawn at any time and without waiting for a compilation of data from a local server.